PENGUASAAN KONSEP SISWA YANG MENGGUNAKAN TEKS PERUBAHAN KONSEPTUAL DALAM MEMPELAJARI HUKUM-HUKUM DASAR KIMIA - Gita Nur Fajriani; Wahyu Sopandi; Asep Kadarohman (Program Studi Pendidikan Kimia, FKIP, Universitas Muhammadiyah Cirebon, 2018)
Conceptual change text is learning material that designed to remedy students’ misconceptions by trigger cognitive conflict and give intelligible, plausible, and fruitful scientific explanation. According to constructivism, students build their own knowledge by themselves by connecting new knowledge with old knowledge that they already own. Conceptual change texts support conceptual change learning based on constructivism theory. This research examines the role of conceptual change text to help students change their conceptions. This research was conducted as quasi experiment with pretest-posttest design to 34 tenth grade students in one of Bandung Barat District public school whose never learn about fundamental laws of chemistry. Written test was used to measure students’ conception. Students’ average score in pretest was 28.8% and 44.1% in posttest. Conceptual change text learning helps students change their initial conceptions into more scientific conceptions. Keywords : fundamental laws of chemistry, conceptual change text, concept mastery